Stable cathode materials
Patent Information
- Application Number
- JP2024209034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-05
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025029044000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is dependent upon and claims priority from U.S. Patent Application No. 62 / 796,950, filed January 25, 2019, U.S. Patent Application No. 16 / 728,379, filed December 27, 2019, U.S. Patent Application No. 16 / 250,615, filed January 17, 2019 (now U.S. Patent No. 10,501,335), U.S. Patent Application No. 16 / 250,762, filed January 17, 2019, U.S. Patent Application No. 16 / 250,622, filed January 17, 2019, and PCT Application No. PCT / US2019 / 057630, filed October 23, 2019, the entire contents of each of which are incorporated herein by reference.
[0002] The present disclosure relates to electrochemically active materials for use in cathodes of secondary batteries.
[0003] 2. Background of the Invention LiMO2 materials based on layered lithium nickel oxide (LiNiO2) are generally desirable as lithium battery cathode materials because they have lower cost, higher capacity, and higher rated capacity than lithium cobalt oxide (LiCoO2). However, pure LiNiO2 materials exhibit poor electrochemical stability and cycling performance. It has been found that replacing some or most of the bulk material Ni in LiNiO2 with various amounts of other metals can provide several capacity and cost advantages over LiNiO2, along with improved electrochemical cycling stability.
[0004] It has also been found that even such substituted LiNiO2 materials may be insufficiently stable when they are charged to high capacities (e.g., ≥ 220 mAh / g), so new materials with improved capacity and / or cycle life are needed.
[0005] Summary of the Invention The following summary is provided to facilitate understanding of some of the innovative features unique to the present disclosure and is not intended to be a complete description. A full understanding of various aspects of the present disclosure can be obtained by taking the entire specification, claims, drawings, and abstract as a whole.
[0006] Electrochemically active particles are provided that contain grain boundaries with a higher electrochemical affinity for lithium that exhibit improved cycling capability at comparable capacity compared to base materials without stabilized grain boundaries. The inventors have found that by selectively increasing the oxidation potential of the grain boundary regions of the particles, thereby increasing the electrochemical affinity for Li, capacity retention can be increased and impedance increase during cycling can be reduced without a significant loss in capacity compared to active materials without grain boundary stabilization.
[0007] Thus, there is provided an electrochemically active particle that may be used as an active material in a cathode of an electrochemical cell (or other such device), the particle comprising a plurality of crystallites comprising a first composition comprising lithium, nickel and oxygen, and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel and oxygen, wherein the grain boundaries have a greater electrochemical affinity for lithium than the crystallites.
[0008] Also provided is an electrochemically active particle comprising a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen, and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen, wherein lithium is present in the grain boundaries in a greater concentration than in the crystallites when the particle is at a state of charge of 10 percent or greater.
[0009] Also provided is an electrochemically active particle comprising a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen, and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; and wherein lithium is present at the grain boundaries in a greater concentration than lithium in the crystallites when an electrode containing the particle is charged to a potential of 4.1 V or greater versus lithium, or wherein lithium is present at the grain boundaries in a greater concentration than lithium in the crystallites at a charge capacity of 40 mAh / g or greater.
[0010] Also provided are electrodes containing one or more electrochemically active particles provided herein.Also provided are electrochemical cells comprising in a cathode one or more electrochemically active particles provided herein.
[0011] The embodiments set forth in the drawings are illustrative and exemplary in nature and are not intended to limit the subject matter defined by the claims. The following detailed description of exemplary embodiments can be understood when read in conjunction with the following drawings, in which like structure is indicated with like reference numerals. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 shows that as the amount of Ni substitution in LiMO2 by other metals increases, the amount of Li extracted from LiMO2 when charged to a given potential decreases. [Diagram 2] FIG. 1 shows that LiMO2 material, which has a lower Ni content than LiNiO2, is delithiated to a lesser extent than LiNiO2 when the materials are charged to the same potential. [Diagram 3] FIG. 13 shows the location of EDS line scans in a thin lamella made from particles of grain boundary modified LiMO2 material of Example 4. [Figure 4]4A and 4B show EDS line scan results for a thin lamella made from particles of the grain boundary modified LiMO2 material of Example 4, where A and C represent the LS1 scan line of FIG. 3 and B and D represent the LS2 scan line of FIG. 3. [Diagram 5] FIG. 1 shows the XRD results of the grain boundary modified LiO2 material of Example 3 and its uniform composition LiMO2-based charged and pristine cathode electrodes. [Figure 6] FIG. 14 shows high-resolution XRD results of the grain boundary modified LiMO2 material of Example 3 and its uniform composition LiMO2-based charged electrode, with peak positions offset and scaled to the (104) peak. [Figure 7] FIG. 1 shows the discharge capacity as a function of cycle number of the grain boundary modified LiMO2 material of Example 1 and its uniform composition LiMO2 precursor during cycling at 45° C. in a full in cell. [Figure 8] FIG. 8 shows a comparison of impedance increase during cycle life measurements at 45° C. for the materials shown in FIG. 7 in a full coin cell. [Figure 9] FIG. 13 shows the discharge capacity as a function of cycle number of the grain boundary modified LiMO2 material of Example 2 and its uniform composition LiMO2 precursor during cycling at 45° C. in a full in cell. [Figure 10] FIG. 10 shows a comparison of impedance increase during cycle life measurements at 45° C. for the materials shown in FIG. 9 in a full coin cell. [Figure 11] FIG. 13 shows the discharge capacity as a function of cycle number for the grain boundary modified LiMO2 materials of Examples 3-5 and their uniform composition LiMO2 precursors during cycling at 45° C. in a full in cell. [Figure 12] FIG. 12 shows a comparison of impedance increase during cycle life measurements at 45° C. for the materials shown in FIG. 11 in a full coin cell. [Figure 13] FIG. 13 shows the increased fracture toughness of low Ni particles in grain boundaries compared to adjacent crystallites. [Figure 14]FIG. 1 illustrates the percent reduction in impedance of materials provided herein according to some embodiments, where the open symbols are bulk material and the filled symbols are selectively Ni depleted at grain boundaries.
[0013] Detailed Description The present inventors have found that electrochemical extraction of high levels of lithium from polycrystalline LiMO2-based materials with a 2D α-NaFeO2-type layered structure results in 2D layers of transition metal atoms within the crystallite grain boundaries reorganizing into a NiO-type rock salt structure, with associated reduction in the oxidation state of the transition metal, loss of oxygen, and introduction of defects such as oxygen vacancies and nickel intermixing between the nickel and lithium layers in the ceramic. This reorganization is initiated at the grain boundaries and propagates deep into the crystallites with repeated cycling. The reorganization may be associated with mechanical damage, including the appearance of cracks between adjacent crystallites. This loss of stability of the material at high levels of lithium extraction leads to a decrease in capacity and an increase in the impedance of the cathode material as it is cycled.
[0014] The present disclosure is based on the discovery that the performance of LiNiO2-based materials can be improved by designing the materials so that more lithium is retained in the grain boundary regions at the end of charging by increasing the oxidation potential of the grain boundary regions, thereby preventing or slowing down the grain boundary reorganization, reducing the susceptibility of NiO and Li2O formation, and reducing the impedance growth rate of these materials as shown in the present disclosure. Thus, the present disclosure provides polycrystalline LiMO2-based materials that include a 2D α-NaFeO2-type layered structure that selectively retains more Li in the grain boundaries than in the internal structure of the crystallites when the material is charged and / or has increased stability in certain regions of the particles to reduce the impedance growth rate during the charge / discharge cycle of the battery and optionally improve cycle life. These materials still release Li from the bulk crystallite structure to provide high cycle capacity even in the charged state, while retaining Li in the grain boundaries that are needed to stabilize the delithiated crystallite material against structural reorganization propagating from the grain boundaries. Retention of higher Li levels in the grain boundaries of a charged material compared to the bulk crystallites can be achieved by selectively increasing the local oxidation potential of the grain boundary regions, thereby preventing the grain boundaries from being delithiated to the same extent as the LiMO bulk crystallites when the material is charged to a given electrochemical potential.
[0015] The nature of the role that increasing the local oxidation potential of the LiMO2 grain boundary composition plays in promoting Li retention at those grain boundaries can be understood by reference to Figure 1, which shows the first charge curves at C / 20 for Li metal anode half cells for cathode materials with varying ratios of Ni as M in LiMO2. These data show that for a series of conventional LiMO2-based Li-ion cathode materials, the potential at which Li is extracted during charging increases, and the amount of Li extracted at a given potential decreases as the percentage of Ni in LiMO2 decreases. Table 1 summarizes the data from Figure 1, which shows that the amount of Li retained when charged to 4.3 V vs. lithium increases with decreasing Ni content of the LiMO2 material. The data in Figure 1 and Table 1 are based on in-house coin cell measurements, except for NM-11, which is based on results from Kang, K., et al., Science, 311 (17), 2006, p.977.
[0016] [Table 1]
[0017] Metals substituting (not selectively localized) for a portion of the Ni in the bulk of the LNO materials in FIG. 1 and Table 1 include Co and Mn, which are representative of metals that effectively reduce the oxidation tendency of LiMO2 compared to Ni when the LiMO2 material is charged, and Al, which is representative of a metal that is not oxidized at all when the LiMO2 material is charged. The relative amounts of such metal substitutions affect the degree of oxidation and Li retention of these bulk materials. Thus, although both NCM811 and NCA have Ni that constitutes 80% of the M in LiMO2, both Co and Mn in NCM811 can be oxidized, whereas Al in NCA cannot be oxidized, resulting in NCA retaining more Li when charged to 4.3 V vs. lithium.
[0018] The various effects of increasing the local oxidation potential in the LiMO2 structure can generally be understood by considering simplified concepts such as the oxidation potential and / or number of electrons of the metal in the context of crystal field theory. In LiMO2 stoichiometry, the average oxidation state of M in the structure is +3. In 2D α-NaFeO2-type layered structures, the M atoms are in a relatively strong octahedral field, so this is d 6 (t 6 2g Crystal field configuration) and d 3 (t 3 2g It is stabilized by metals with the electron count of 0.01 to 0.01. 3+ d 7 whereas Co 3+ d 6 Therefore, when LiNiO2 is oxidized, it has a stable t 6 2g While LiCoO2 acquires a crystal field configuration, when it is oxidized, 6 2g LiNiO2 is more prone to oxidation than LiCoO2 due to loss of crystal field configuration. Published X-ray absorption studies have shown that the replacement of Ni with Mn results in Mn oxidizing to the stable +4 oxidation state (t 3 2g crystal field configuration) and is housed in the +2 oxidation state (t 6 2g e 2 g It has been shown that the charge is compensated by Ni in the crystal field configuration. Therefore, the Ni atom is placed in a more stable t 6 2g To oxidize to the structure, two electrons and a charge compensating Li + While oxidation of Ni atoms in LiNiO2 proceeds by a more facile single-electron / single-ion process, the Al in LiMO2 is already in the 3+ oxidation state and does not have an available 4+ oxidation state at realistic battery cathode material potentials.
[0019] The above discussion of oxidation and Li retention in bulk LiMO2 cathode materials shows how increasing the oxidation potential of the grain boundaries of LiMO2 materials can result in greater retention of Li in the grain boundaries than in the bulk crystallites when these materials are charged. Thus, for example, if a material with LNO bulk crystallite composition (M in LiMO2 is 100% Ni) has grain boundaries with a composition corresponding to one of the other materials in Figure 1, the reconstructed data of Figure 1 plotted in Figure 2 shows how much more Li is retained in the grain boundaries compared to the amount of Li retained in the LNO bulk crystallites when the material is oxidized (charged) to a given potential. This figure shows that at any potential or state of charge up to 4.3 V vs. lithium, the grain boundaries retain more Li than the bulk crystallites. Similarly, these data can be normalized to the Li content of one of the other materials to show that materials with, for example, NCM(811) bulk crystallites and NCM(523) grain boundaries also retain more Li in the grain boundaries than the bulk crystallites when these are charged. It should be noted that 4.3 V vs. lithium is illustrative and that even when the material is charged to a potential higher or lower than 4.3 V vs. lithium, it can still retain more Li in the grain boundaries than in the bulk.
[0020] The term "state of charge" (SoC) as used herein is the charge level of a battery relative to its capacity. The units of SoC are percentage points (0%=empty or discharged; 100%=full or charged). For the lithium nickel oxide materials provided herein, full charge is achieved at a potential of 4.1 V or greater, optionally 4.2 V or greater, optionally 4.3 V or greater, and optionally 4.4 V or greater vs. Li.
[0021] The term "electrochemical affinity" for lithium as used herein is defined as the tendency to retain lithium when oxidized to a particular potential or voltage. Thus, a material with a high electrochemical affinity will retain more lithium when charged to a particular potential than a material with a low electrochemical affinity for lithium. This potential can be a reasonable range of potentials. A material with a high electrochemical affinity for lithium means that the material (or a portion of the material) has a higher lithium content compared to a material with a low electrochemical affinity when both materials are at the same potential.
[0022] Thus, there is provided a particle comprising a plurality of crystallites comprising a first composition containing lithium, nickel and oxygen and having a layered α-NaFeO2-type structure, and grain boundaries between adjacent crystallites of the plurality of crystallites comprising a second composition having a layered α-NaFeO2-type structure, a cubic structure, a spinel structure, a monoclinic structure, or a combination thereof, wherein the second composition has a higher electrochemical affinity for lithium compared to the first composition and / or compared to a material having a lower electrochemical affinity when both materials are at the same potential; and / or nickel is present in a lower concentration in the second composition than nickel in the first composition.
[0023] According to some aspects of the present disclosure, there is also provided a particle comprising a plurality of crystallites comprising a first composition containing a layered-layered composition having the general formula zLiMO2·(1-z)Li2M’O3, where z ranges from 0.7 < z < 1.0, optionally from 0.8 < z < 0.95 moles per mole of the composition. The layered-layered material includes grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries including a second composition having a layered α-NaFeO2-type structure, a cubic structure, a spinel structure, a monoclinic structure, or a combination thereof. In some exemplary aspects, M can include Ni, Co, Mn, or a combination thereof, and M' can include one or more of Mn, Ti, or Cr. Note that the oxidation potential and electrochemical affinity of the grain boundary region of the layered-layered material can be as described for the other materials shown herein.
[0024] In the layered-layered material, M optionally includes Ni alone or in combination with one or more of Co, Mn, V, or Fe. The Ni component of M is optionally from 0.3 moles to 0.95 moles per mole of M. When Co is present in M, it is optionally present from 0 moles to 0.33 moles per mole of M. When Mn is present in M, it is optionally present from 0.05 moles to 0.8 moles per mole of M. In some aspects, M includes from 0.3 moles to 0.95 moles of Ni per mole of M, from 0 moles to 0.33 moles of Co per mole of M, and from 0.05 moles to 0.5 moles of Mn per mole of M. In the layered-layered material, M' includes Mn alone or in addition to one or more of Ti, Zr, Ru, Re, and Pt.
[0025] In compositions having a layered α-NaFeO2 type structure, hexagonal metal oxide layers are separated by alkali metal (e.g. Li) planes. The metal oxide layers form metal-centered oxygen octahedra separated by alkali metal ions. These metal oxide layers are laterally offset to provide a three-layer structure. In layered α-NaFeO2 type structures, the alkali metal atoms occupy so-called "3a" sites (x=0, y=0, z=0) in the structure, the metal atoms occupy "3b" sites (x=0, y=0, z=0.5), and the oxygen atoms occupy "6c" sites (x=0, y=0, z=0.25). The atomic coordinates and cell parameters may vary depending on the composition. Compositions of this structure type may have cell parameters where a is about 2.75 to about 2.95 angstroms (Å) and c is about 13.9 to about 14.6 Å. By selectively substituting metals with higher oxidation potentials than Ni at the 3b sites of the grain boundaries, the grain as a whole can be stabilized compared to unstabilized material of otherwise identical bulk composition.
[0026] According to some embodiments, the materials provided herein include particles that include a plurality of crystallites, each of which includes a first composition. Particles formed from a plurality of crystallites may be referred to as secondary particles. The particles provided herein are uniquely tailored to have grain boundaries between primary crystallites that include a second composition. Stabilizing these grain boundaries by increasing the electrochemical affinity for Li compared to the bulk crystallites results in improved performance and cycle life of cells that contain the particles as a cathode component, and results in particles that exhibit reduced impedance growth during cycling.
[0027] It is understood that the particles include grain boundaries formed from or including a second composition, the second composition differing from the first composition in that the electrochemical affinity for Li in the second composition is increased compared to the first composition defining the crystallites of the secondary particles, and / or in that the second composition has a lower concentration of Ni compared to the first composition. Optionally, the particles provided herein can maintain more Li in the grain boundaries than in the crystallites at any particular state of charge greater than zero. Optionally, the particles provided herein can maintain more Li in the grain boundaries than in the crystallites when the particles are at a given potential or over a range of potentials. Optionally, the materials provided have a lower concentration of Ni in the grain boundary regions compared to adjacent crystallites. Optionally, the materials provided include an additional outer coating layer that can be disposed on the outer surface of the secondary particles to obtain coated secondary particles.
[0028] In some embodiments, an electrochemically active particle is provided that includes a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein the grain boundaries have a higher electrochemical affinity for lithium than the crystallites. The higher electrochemical affinity for Li at the grain boundaries results in a higher concentration of Li at the grain boundaries compared to the crystallites at any particular state of charge.
[0029] Also provided is an electrochemically active particle comprising: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein nickel is present at the grain boundaries at a concentration that is lower than the nickel concentration within the crystallites.
[0030] Optionally, the molar content of lithium per mole of the second composition defining the grain boundaries relative to the molar content of Li per mole of the first composition defining the crystallites is found to be 10% or more, optionally 20% or more, optionally 30% or more, optionally 40% or more, optionally 50% or more, optionally 60% or more, optionally 70% or more, optionally 80% or more, optionally 90% or more, optionally 95% or more, optionally 96% or more, optionally 97% or more, optionally 98% or more, optionally 99% or more, optionally at 100% state of charge.
[0031] In some embodiments, an electrochemically active particle is provided that includes: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein the grain boundaries have a higher electrochemical affinity for lithium than the crystallites at a state of charge of 10% or greater.
[0032] In some embodiments, an electrochemically active particle is provided that includes: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein the grain boundaries have a higher electrochemical affinity for lithium than the crystallites at a state of charge of 80% or greater.
[0033] In some embodiments, an electrochemically active particle is provided that includes: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein the grain boundaries have a higher electrochemical affinity for lithium at 100% state of charge than the crystallites.
[0034] Also provided is an electrochemically active particle comprising: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein lithium is present in the grain boundaries in a greater concentration than lithium within the crystallites when the particle is at a state of charge of 10 percent or greater.
[0035] Optionally, the molar concentration of lithium per mole of the second composition defining the grain boundaries relative to the molar concentration of Li per mole of the first composition defining the crystallites is found to be higher than at least 10%, optionally at least 20%, optionally at least 30%, optionally at least 40%, optionally at least 50%, optionally at least 60%, optionally at least 70%, optionally at least 80%, optionally at least 90%, optionally at least 95%, optionally at least 96%, optionally at least 97%, optionally at least 98%, optionally at least 99%, optionally at 100% state of charge.
[0036] Also provided is an electrochemically active particle comprising: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein lithium is present in the grain boundaries in a greater concentration than in the crystallites when the particle is at a state of charge of 20 percent or greater.
[0037] Also provided is an electrochemically active particle comprising: a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein when the particle is at a state of charge of 80 percent or greater, lithium is present in the grain boundaries in a greater concentration than lithium within the crystallites.
[0038] Also provided is an electrochemically active particle that may be used in a cathode of an electrochemical cell that may include a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein lithium is present at the grain boundaries in a greater concentration than lithium in the crystallites when an electrode containing the particle is charged to a potential of 4.00 V or greater versus lithium.
[0039] In some embodiments, a Ni mole fraction in the second region of 0.95 or less improves the electrochemical performance of the material. It has been found that reducing the Ni level in the grain boundary regions of the particles enhances the stability of the overall particle. Optionally, the ratio of the Ni mole fraction in the second composition to the Ni mole fraction in the first composition ranges from 0.95 to 0.5. Optionally, the ratio of the Ni mole fraction in the second composition to the Ni mole fraction in the first composition is 0.95 or less, optionally 0.90 or less, optionally 0.85 or less, optionally 0.80 or less, optionally 0.75 or less, optionally 0.7 or less, optionally 0.65 or less, optionally 0.6 or less, optionally 0.55 or less.
[0040] Optionally, when an electrode containing the particles is charged to a potential of 4.1 V or more versus lithium, lithium is present in the grain boundaries (second composition) at a higher concentration than lithium in the crystallites (first composition). Optionally, when an electrode containing the particles is charged to a potential of 4.2 V or more versus lithium, lithium is present in the grain boundaries at a higher concentration than lithium in the crystallites. Optionally, when an electrode containing the particles is charged to a potential of 4.25 V or more versus lithium, lithium is present in the grain boundaries at a higher concentration than lithium in the crystallites. Optionally, when an electrode containing the particles is charged to a potential of 4.3 V or more versus lithium, lithium is present in the grain boundaries at a higher concentration than lithium in the crystallites.
[0041] The increase in the amount of Li retained in the second composition at the grain boundaries compared to the bulk is optionally at least 0.02 moles Li per mole of the second composition at the potentials set forth in the previous paragraph. Optionally, the moles of Li per mole of the second composition is greater than the moles of Li per mole of the first composition by at least 0.01, optionally at least 0.02, optionally at least 0.05, optionally at least 0.1, optionally at least 0.15, optionally at least 0.2, optionally at least 0.25, optionally at least 0.3 at the potentials set forth in the previous paragraph.
[0042] In some embodiments, the elemental compositions of the first and second compositions are identical except for the relative amounts of each of the individual metal components, with the proviso that the amount of Ni in the second composition is less than the amount of Ni in the first composition. In other embodiments, the second composition includes one or more additional metals not present in the first composition, which can substitute for Ni in the crystal lattice of the second regions, thereby promoting increased order, improved cycle life, and reduced internal resistance in these regions.
[0043] Also provided is an electrochemically active particle that may be used in a cathode of an electrochemical cell that may include a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; wherein lithium is present in the grain boundaries in a greater concentration than in the crystallites at a charge capacity of the particle of 40 mAh / g or greater.
[0044] When the particles are charged to a capacity optionally of 50 mAh / g or more, optionally 60 mAh / g or more, optionally 70 mAh / g or more, optionally 80 mAh / g or more, optionally 90 mAh / g or more, optionally 100 mAh / g or more, optionally 110 mAh / g or more, optionally 120 mAh / g or more, optionally 130 mAh / g or more, optionally 140 mAh / g or more, optionally 150 mAh / g or more, optionally 160 mAh / g or more, optionally 170 mAh / g or more, optionally 180 mAh / g or more, optionally 190 mAh / g or more, optionally 200 mAh / g or more, optionally 220 mAh / g or more.
[0045] Optionally, at a given potential or charge capacity of 40 mAh / g or greater, the moles of Li per mole of the second composition is 0.01, optionally 0.02, optionally 0.05, optionally 0.1, optionally 0.15, optionally 0.2, optionally 0.25, optionally 0.3 greater than the moles of Li per mole of the first composition. Optionally, the increase in the amount of Li retained in the second composition at the grain boundaries compared to the amount of Li retained in the first composition at the crystallites is 0.01 moles Li per mole of the second composition or greater, optionally 0.15 moles Li per mole of the second composition or greater, optionally 0.2 moles Li per mole of the second composition or greater, optionally 0.25 moles Li per mole of the second composition or greater, optionally 0.3 moles Li per mole of the second composition or greater. Optionally, the amount of Li retained in the second composition is greater than the amount of Li retained in the first composition at a charge capacity of the particles of 50 mAh / g or more, optionally 60 mAh / g, optionally 70 mAh / g or more, optionally 80 mAh / g or more, optionally 90 mAh / g or more, optionally 100 mAh / g or more, optionally 110 mAh / g or more, optionally 120 mAh / g or more, optionally 130 mAh / g or more, optionally 140 mAh / g or more, optionally 150 mAh / g or more, optionally 160 mAh / g or more, optionally 170 mAh / g or more, optionally 180 mAh / g or more, optionally 190 mAh / g or more, optionally 200 mAh / g or more, optionally 220 mAh / g or more, optionally by an amount as described above.
[0046] Optionally, a particle comprising a second composition present at the grain boundary regions, optionally only at the grain boundary regions, the second composition having a lower concentration of Ni compared to the concentration of Ni in the first composition of the crystallites, enhances the physical stability of the particle and enhances fracture toughness or fracture resistance.
[0047] One way to measure particle stability is by measuring fracture toughness. Measurement of fracture toughness can be done by placing a known amount of particles as provided herein into a die, applying an appropriate amount of pressure, optionally 900 MPa, and then measuring the increase in the amount of fines produced in the material by applying pressure. This serves as a direct measurement of physical particle stability that the inventors have found to correspond directly with the percentage decrease in impedance increase during cycling. Optionally, the amount of fines in the particles obtained after applying pressure of 890 MPa or 900 MPa increases by less than 50 percent by number. Measurement of fines in the sample after applying pressure can be done by particle size analysis by recognized techniques. Fines as defined herein are particles (or particle fragments) having a size of 3.5 μm or less as measured by particle size analysis. For example, in some particle size analyses, the absolute number of particles is known and the percent pass is the number of fines with respect to the total particle number determined in the analysis. In some embodiments, particle surface area correlates with improved performance, such as cycle life or reduction in impedance increase. In this disclosure, increased surface area can be measured by techniques such as Brunauer-Emmett-Teller (BET) surface area measurement. The method used here relates to the count of fines of size 3.5 μm or less as a rapid and easily reproducible way of determining improved particle performance.
[0048] As an exemplary method of quantifying the percentage fraction of fines, a sample of the granular material can be ground in a 2 cm diameter die in a hydraulic press to the desired pressure. A total mass of 2.5 g of powder can be placed in the die and crushed to form pellets. The pellets can then be placed in 20 mL of water and subjected to ultrasonic dispersion for 30 minutes. After dispersion, a small amount of the dispersed slurry can be placed in a Malvern Mastersizer3000 laser light particle size analyzer equipped with a liquid cell. To ensure complete dispersion of the fines, the ultrasonic function can be used during the measurement and an average of five measurements can be used to calculate the final result. The distribution can be calculated using the properties of NiO taken from the instrument's library.
[0049] The percentage of fines produced by applying pressure to the die decreases as the relative Ni concentration in the grain boundaries compared to the crystallites decreases. Optionally, the percentage of fines produced by applying pressure to the die is less than or equal to 50, 40, 35, 30, 25, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, or 2 percent. In some embodiments, the concentration of nickel in the second composition is less than the concentration of nickel in the first composition, and the fracture resistance is such that less than 15% fines are produced when the material is pressed to a pressure of 900 MPa.
[0050] Optionally, when the material is an NCA material having 80 atomic percent or more Ni in the bulk particles, the number of fines produced is less than 15 percent, optionally less than 14 percent, optionally less than 13%, optionally less than 12%, optionally less than 11%, optionally less than 10%, optionally less than 9%, optionally less than 8%, optionally less than 7%, optionally less than 6%. Optionally, when the material is an NCA material having 90 atomic percent or more Ni, the number of fines produced is less than 7%, optionally less than 6 percent, optionally less than 5%, optionally less than 4%, optionally less than 3%. Optionally, when the material is an NCM material having 80 atomic percent or more Ni, the number of fines produced is less than 6 percent, optionally less than 5 percent, optionally less than 4 percent, optionally less than 3 percent, optionally less than 2 percent.
[0051] In some embodiments of the particles provided herein, a first composition defining the crystallites of the secondary particles is a polycrystalline layered structure lithiated metal oxide defined by a composition defined by Formula I: Li 1+x MO 2+y (I) and optionally a cell or battery formed therefrom, wherein -0.1≦x≦0.3 and -0.3≦y≦0.3 when in a discharged state, or -0.9≦x≦0.1 and -0.3≦y≦0.3 when in a charged state. In some embodiments, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.0 9 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.30 or more. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3.Optionally, y is -0.30 or more, -0.29 or more, -0.28 or more, -0.27 or more, -0.26 or more, -0.25 or more, -0.24 or more, -0.23 or more, -0.22 or more, -0.21 or more, -0.20 or more, -0.19 or more, -0.18 or more, -0.17 or more, -0.16 or more, -0.15 or more, -0.14 or more, -0.13 or more, -0.12 or more, -0.11 or more, -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, 0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.3 or more.
[0052] It is understood that in some embodiments, Li need not be exclusively Li, but may be partially replaced with one or more elements selected from the group consisting of Mg, Sr, Na, K, and Ca. The one or more elements replacing Li are optionally present at 10 atomic % or less, optionally 5 atomic % or less, optionally 3 atomic % or less, optionally 2 atomic percent or less, these percentages being based on the total Li in the material.
[0053] M, as depicted in the first composition, includes Ni. The amount of Ni in the first composition is optionally between 10 atomic percent and 100 atomic percent (at%) of the total M. Optionally, the Ni content of M is 75 at% or greater. Optionally, the Ni content of M is 80 at% or greater. Optionally, the Ni content of M is 85 at% or greater. Optionally, the Ni content of M is 90 at% or greater. Optionally, the Ni content of M is 95 at% or greater. Optionally, the Ni content of M is 75 at% or more, 76 at% or more, 77 at% or more, 78 at% or more, 79 at% or more, 80 at% or more, 81 at% or more, 82 at% or more, 83 at% or more, 84 at% or more, 85 at% or more, 86 at% or more, 87 at% or more, 88 at% or more, 89 at% or more, 90 at% or more, 91 at% or more, 92 at% or more, 93 at% or more, 94 at% or more, 95 at% or more, 96 at% or more, 97 at% or more, 98 at% or more, 99 at% or more, 99.5 at% or more, 99.9 at% or more, or 100 at% or more.
[0054] In some embodiments, M in the first composition is Ni alone or in combination with one or more additional elements. The additional element is optionally a metal. Optionally, the additional element may include or be one or more of Mg, Sr, Co, Al, Ga, Ca, Cu, Zn, Mn, V, Ba, Y, Nb, Zr, Ti, Cr, Fe, Mo, W, B, and any combination thereof. In certain embodiments, the additional element may include Mg, Co, Al, or a combination thereof. Optionally, the additional element may be Mg, Al, V, Ti, B, or Mn, or a combination thereof. Optionally, the additional element is selected from the group consisting of Mg, Al, V, Ti, B, or Mn. Optionally, the additional element is selected from the group consisting of Mg, Co, and Al. Optionally, the additional element is selected from the group consisting of Ca, Co, and Al. In some embodiments, the additional element is Mn or Mg, or both Mn and Mg. Optionally, the additional element is Mn, Co, Al, or any combination thereof. Optionally, the additional element includes Co and Mn. Optionally, the additional element is Co and Al. Optionally, the additional element is Co.
[0055] The additional element of the first composition may be present in an amount of about 1 to about 90 at% of the total M, specifically about 5 to about 80 at% of M in the first composition, more specifically about 10 to about 70 at%. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, specifically about 2 to about 18 at%, more specifically about 4 to about 16 at% of M in the first composition. In some illustrative examples, M is about 75 to 100 at% Ni, 0 to 15 at% Co, 0 to 15 at% Mn, and 0 to 10 at% of the additional element.
[0056] Within a polycrystalline material, each crystallite may have any suitable shape, which may be the same or different within each grain. Furthermore, the shape of each crystallite may be the same or different in different grains or within different particles. Due to the nature of the crystal, the crystallites may be faceted, the crystallites may have multiple flat surfaces, and the shape of the crystallites may approximate a geometric shape. In some embodiments, the crystallites may be fused with adjacent crystallites that have mismatched crystal faces. The crystallites may optionally be polyhedral. The crystallites may have a linear shape, and when viewed in cross section, some or all of the crystallites may be linear. The crystallites may be square, hexagonal, rectangular, triangular, or combinations thereof. The crystallites are optionally single crystals, and the grains are optionally aggregates of single crystals.
[0057] The particle includes a grain boundary separating two adjacent crystallites. The grain boundary includes a second composition. In some embodiments, the grain boundary includes a second composition having an α-NaFeO2-type structure having general formula II: Li 1+x M'O 2+y (II) where M' is defined as M in the first composition, but with a relatively low number of moles of Ni per mole of LiMO2. The Ni sites in the crystal structure are substituted with one or more substitution elements that increase the electrochemical affinity of the structure for lithium compared to the unsubstituted material, such that the amount of substitution element is greater in moles per mole concentration in the second composition than in the first composition, optionally -0.6≦x≦-0.2 at a state of charge of 80% or greater or a charge capacity of 150 mAh / g or greater. In some embodiments, x is -0.6, optionally -0.65, optionally -0.7, optionally -0.75, optionally -0.8, optionally -0.9, or optionally -0.95. In some embodiments, y is −0.3, optionally −0.2, optionally −0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is -0.30 or more, -0.29 or more, -0.28 or more, -0.27 or more, -0.26 or more, -0.25 or more, -0.24 or more, -0.23 or more, -0.22 or more, -0.21 or more, -0.20 or more, -0.19 or more, -0.18 or more, -0.17 or more, -0.16 or more, -0.15 or more, -0.14 or more, -0.13 or more, -0.12 or more, -0.11 or more, -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0 0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.3 or more.When particles having the stabilized second composition are included in a cathode that is electrochemically charged to about 4.3 V (which may be lower or higher based on the specific application), improved performance is observed due to increased electrochemical affinity for Li compared to crystallites.
[0058] Optionally, the Ni in the second composition may range from 0 to 0.99 moles per mole of M' in the second composition. Optionally, M' in the second composition does not include Ni. Optionally, the amount (i.e., relative concentration) of Ni in the second composition is less than the amount of Ni in the first composition in relative atomic percent (for each composition in which Ni is present). Optionally, the Ni component of M' is 1 mole or less per mole of M'. Optionally, the Ni component of M' is 0.5 moles or less per mole of M'. Optionally, the Ni component of M' is 0.10 moles or less per mole of M'. Optionally, the Ni component of M' is 0.20 moles or less per mole of M'. Optionally, the Ni component of M' is 0.75 moles or less per mole of M'. Optionally, the Ni component of M' is 0.80 moles or less per mole of M'. Optionally, the Ni content of M' is less than or equal to 0.85 moles per mole of M'. Optionally, the Ni content of M' is less than or equal to 0.90 moles per mole of M'. Optionally, the Ni content of M' is less than or equal to 0.95 moles per mole of M'. Optionally, the Ni component of M' is 0.75 moles or less per mole of M', 0.76 moles or less per mole of M', 0.77 moles or less per mole of M', 0.78 moles or less per mole of M', 0.79 moles or less per mole of M', 0.80 moles or less per mole of M', 0.81 moles or less per mole of M', 0.82 moles or less per mole of M', 0.83 moles or less per mole of M', 0.84 moles or less per mole of M', 0.85 moles or less per mole of M', 0.86 moles or less per mole of M', 0.87 moles or less per mole of M', mol or less, 0.88 mol or less per mole of M', 0.89 mol or less per mole of M', 0.90 mol or less per mole of M', 0.91 mol or less per mole of M', 0.92 mol or less per mole of M', 0.93 mol or less per mole of M', 0.94 mol or less per mole of M', 0.95 mol or less per mole of M', 0.96 mol or less per mole of M', 0.97 mol or less per mole of M', 0.98 mol or less per mole of M', 0.99 mol or less per mole of M', or 0.999 mol or less per mole of M'.
[0059] In the materials provided herein, the nominal or total compounding composition of the secondary particles (e.g., characterized by inductively coupled plasma (ICP)), optionally the first composition, or optionally the second composition, is defined by the formula LiMO2, where M is Ni, and optionally the one or more substitution elements in the second composition must include at least one element substituting Ni in the crystal structure that confers a greater electrochemical affinity for Li to the second composition than to the first composition. The mole fraction of the substitution elements in the first composition that defines the composition of the crystallite, if present, is lower than the separate or total mole fraction of the substitution elements in the entire grain composition as determined by ICP. The separate or total mole fraction of the substitution elements in the first composition may be zero. The separate or total mole fraction of the substitution elements in the second composition that defines the grain boundaries is higher than the separate or total mole fraction of the substitution elements in the entire grain as measured by ICP.
[0060] Examples of substitution elements that may be included in M' of formula II and that can promote Li retention at the grain boundaries of charged Ni-rich LiMO2 cathode materials include various elements that can substitute for Ni in the LiM'O2 structure. Such doping elements can promote Li retention (i.e., greater electrochemical affinity for Li) by being more resistant to oxidation (having a higher oxidation potential) than the Ni atoms they replace, or by stabilizing the structure against oxidation, or by inductively raising the oxidation potential of nearby Ni atoms. 3+ If the trivalent (3+) ions of doping elements that can directly substitute for Ni are less likely to be oxidized than Ni ions when the material is charged, they will promote retention of Li. The substitution of Al(III) for Ni(III) is one example. 3+When 2+ ions substituting for Ni are hard to oxidize, they are charge compensated by Ni ions in the 2+ state, and their inductive effect increases the potential at which these Ni ions are oxidized to the 4+ state. Substitution of Ni(III) by Mn(IV) is an example. Alternatively, when the 2+ ions substituting for Ni are difficult to oxidize, they are charge compensated by Ni ions in the 4+ state. Substitution of Ni(III) by Mg(II) is an example. To substitute for Ni in the LiM'O2 structure, the doping ions must be of comparable size to the Ni ions, and to promote Li retention, they must raise the local oxidation potential. The relative influence of a given ion on the oxidation potential is often determined by the relative effect of Ni 3+ It can be estimated from the ionization energy compared to Ni. 3+ Ions of comparable size and equal or greater ionization energy can potentially function to stabilize the grain boundaries of oxidized cathodes by increasing Li retention. The table below shows the ionization energies and ionic radii in hexacoordinated (octahedral environment) for example ions that can stabilize the grain boundaries of charged high Ni LiMO2 cathode materials by increasing grain boundary retention of Li.
[0061] [Table 2]
[0062] In the second composition, M' further comprises one or more substitution elements that may be selected from a group that is less oxidized than nickel when electrochemically charged to 4.3V or more versus a Li metal anode. In one example, M' may comprise Ni and a combination of Co and Mn that is less oxidized than nickel when charged to 4.3V. In another embodiment, M' may comprise Ni and one or more elements selected from the group including Mn, Cr, Fe, Ti, V, Co, Cu, Zn, Zr, Nb, Sb, W, Sc, Al, Mo, Y, etc. that are less oxidized than Ni when charged to 4.3V versus lithium metal. Optionally, M' excludes only Co, only Al, or a combination of Co and Al with Ni, and Co, Al, or both may be present with doping of one or more additional substitution elements as set forth herein. In some embodiments, M' can include an element selected from the group of elements that do not oxidize when charged to 4.3 V versus lithium, such as Y, Sc, Ga, In, Tl, Si, Ge, Sn, Pb, etc.
[0063] It should be noted that 4.3V is chosen only as a representative example. The voltages can be lower (e.g., 4.0, 4.1, 4.2 vs. Li) or higher (4.35, 4.4, 4.5V, 4.6V, 4.7V vs. Li). The specific voltages of interest depend on the operating potential of the battery when the cathode is paired with the anode.
[0064] In some embodiments, the second composition of the grain boundaries has a greater electrochemical affinity for Li, such that when an electrode containing the particles is charged to a potential of 4.1 V or more versus lithium, optionally 4.2 V or more versus lithium, optionally 4.3 V or more versus lithium, the grain boundaries retain more than 0.15 moles of lithium per mole of the second composition at said potential.
[0065] In some embodiments, the second composition at the grain boundaries has a greater electrochemical affinity for Li, such that when an electrode containing the particles is charged to a capacity of 100 mAh / g or greater, optionally 200 mAh / g or greater, the grain boundaries retain greater than 0.15 moles of lithium per mole of the second composition at said potential.
[0066] Optionally, at a potential or capacity as set forth herein, the second composition comprises: lithium in an amount of about 0.1 to about 1.3 moles, specifically about 0.15 to about 1.2 moles, more specifically about 0.3 to about 1.1 moles per mole of the second composition; nickel in an amount of about 0.1 to about 0.999 moles, specifically about 0.2 to about 0.90 moles, more specifically about 0.3 to about 0.85 moles per mole of the second composition; manganese in an amount of about 0.02 to about 0.99 moles, specifically about 0.04 to about 0.90 moles, more specifically about 0.06 to about 0.80 moles per mole of the second composition; and oxygen in an amount of about 1.7 to about 2.3 moles, specifically about 1.8 to about 2.2 moles, more specifically about 1.9 to about 2.1 moles per mole of the second composition.
[0067] The second composition can further include an additional metal, and the additional metal of the second composition can be present in an amount of about 0.01 to about 0.9 moles, specifically about 0.05 to about 0.8 moles, and more specifically about 0.1 to about 0.7 moles, per mole of the second composition. In one embodiment, the additional metal of the second composition can be present in an amount of about 0.01 to about 0.2 moles, specifically about 0.02 to about 0.18 moles, and more specifically about 0.04 to about 0.16 moles, per mole of the second composition.
[0068] The additional metal of the second composition may include Mg, Sr, Ca, Cu, Zn, Mn, Al, V, Ba, Zr, Ti, Cr, Fe, Mo, B, or a combination thereof. Optionally, the additional metal of the second composition includes Mg, Al, V, Ti, B, Zr, or Mn, or a combination thereof. Optionally, the additional metal of the second composition includes Mg, Al, V, Ti, B, Zr, or Mn. Specific reference is made to an embodiment in which the additional metal of the second composition is Mn or Mg. Optionally, the additional metal of the first composition and the additional metal of the second composition are each Mg. Optionally, the first composition further comprises Mn, wherein the Mn is present in the first composition in an amount of about 0.01 to about 0.6 moles, specifically about 0.02 to about 0.5 moles, per mole of the first composition, and the second composition comprises Mn, wherein the Mn is present in the second composition in an amount of about 0.01 to about 0.6 moles, specifically about 0.02 to about 0.5 moles, per mole of the second composition.
[0069] The grain boundaries are between adjacent crystallites, on the surfaces of the crystallites, and comprise or consist of a second composition. The second composition has a layered α-NaFeO2 type structure, a cubic structure, a monoclinic structure, or a combination thereof. As described above, the grain boundaries include at least one substitution element such that the electrochemical affinity of the second composition for Li is greater than the electrochemical affinity of the first composition found in the bulk crystallite. Particular reference is made to embodiments in which the grain boundaries comprise or consist of a layered α-NaFeO2 type structure.
[0070] The shape of a grain boundary is defined by the shape of the crystallites adjacent to the grain boundary. The shape of a grain boundary can be approximated by a geometric shape. The grain boundary can have a linear shape, and when viewed in cross section, the grain boundary can be linear. The grain boundary can be square, hexagonal, rectangular, triangular, or a combination thereof.
[0071] The direction of the surface of the grain boundary corresponds to the direction of the surface of the adjacent crystallite. The surface of the grain boundary and the surface of the crystallite may have any of a variety of orientations with respect to the outer surface of the secondary particle. Thus, the direction of the surface of the crystallite and the surface of the grain boundary may be parallel to the direction of the nearest outer surface of the secondary particle, or may be different. In some embodiments, the direction of the tangent of the nearest outer surface of the particle is different from the direction of the surface of the grain boundary and the direction of the surface of the adjacent particle.
[0072] The grain boundaries can intersect to form an angle between them. In some embodiments, the first grain boundary and the second grain boundary are disposed on adjacent faces of the crystallite. The first grain boundary and the second grain boundary intersect at an angle E. The angle E can be defined by the shape of the crystallite on which the first grain boundary and the second grain boundary are disposed. In general, the shape of the crystallite is influenced by the crystal structure of the crystallite. Without wishing to be bound by theory, it is understood that the angle between the first grain boundary and the second grain boundary is influenced by the crystal structure of the first composition, since the crystal structure of the first composition governs the shape of the crystallite. The first and second grain boundaries can intersect at any angle, specifically about 10 to about 170 degrees, specifically about 20 to about 160 degrees, more specifically about 30 to about 150 degrees, as long as the angle is consistent with the crystal structure of the first composition.
[0073] The dimensions of the grain boundary are not particularly limited. The length and width of the grain boundary may each independently be about 10 to about 1000 nm, specifically about 60 to about 900 nm, more specifically about 70 to about 800 nm. The length and width of the grain boundary are perpendicular to each other and parallel to the surfaces of adjacent crystallites. The thickness of the grain boundary may be about 0.5 to about 30 nm, specifically about 1 to about 20 nm, more specifically about 1 to about 10 nm. The thickness of the grain boundary may be substantially perpendicular to the length and width of the grain boundary and perpendicular to the surfaces of adjacent crystallites. The composition of the grain boundary may be substantially uniform or may vary along the thickness.
[0074] The average grain boundary length and the average grain boundary width of the multiple grain boundaries may each independently be about 10 to about 1000 nm, specifically about 60 to about 900 nm, and more specifically about 70 to about 800 nm.Similarly, the average grain boundary thickness of the multiple grain boundaries may be about 0.1 to about 30 nm, specifically about 1 to about 20 nm, and more specifically about 1 to about 10 nm.
[0075] Optionally, the particles provided herein include an outer coating, such as a passivation layer or a protective layer, which may be provided on the outer surface of the secondary particles to obtain coated secondary particles. The coating may completely or partially cover the secondary particles. The outer coating layer may be amorphous or crystalline. The outer coating layer may include an oxide, sulfate, phosphate, pyrophosphate, fluorophosphate, carbonate, fluoride, oxyfluoride, or combinations thereof of a metal, such as Zr, Al, Ti, Al, B, or Si, or combinations thereof. Optionally, the outer coating layer includes a borate, an aluminate, a silicate, a fluoroaluminate, or combinations thereof. Optionally, the outer coating layer includes a carbonate. In one embodiment, the layer includes ZrO2, Al2O3, TiO2, AlPO4, AlF3, B2O3, SiO2, Li2O, Li2CO3, or combinations thereof. Layers including AlPO4 or Li2CO3 are specifically mentioned. Optionally, the outer coating layer comprises an oxide of one or more elements selected from Al, Zr, Y, Co, Ni, Mg, and Li. Optionally, the outer coating layer comprises a fluoride comprising one or more elements selected from Al, Zr, and Li. Optionally, the outer coating layer comprises a carbonate comprising one or more elements selected from Al, Co, Ni, Mn, and Li. Optionally, the outer coating comprises a sulfate comprising one or more elements selected from Al, Co, Ni, Mn, and Li. Optionally, the outer coating comprises a phosphate comprising one or more elements selected from Al and Li. The layer can be applied by any process or technique that does not adversely affect the desired properties of the secondary particles. Exemplary methods include, for example, spray coating and dip coating.
[0076] The secondary particles can be formed by a multi-step process whereby particles of a first composition are formed and calcined to form crystallites with low defect α-NaFeO2 structure and optionally defined grain boundaries. The resulting secondary particles are then subjected to a liquid process to apply one or more substitution elements at desired concentration levels, followed by drying and then a second calcination, resulting in selective migration of precipitated species of the substitution elements at the surface to the grain boundaries, thereby forming secondary particles with stable grain boundaries that have a higher electrochemical affinity for Li than the bulk crystallites. According to the method of producing secondary particles having bases of Ni, Co, and Mg provided herein as an example, the formation may include combining a lithium compound with one or more metal or semimetal hydroxide precursor compounds (e.g., combined Ni, Co, and Mg, previously produced by a coprecipitation reaction, etc.) to form a mixture; heat treating the mixture at about 30 to about 200°C to form a dry mixture; heat treating the dried mixture at about 200 to about 500°C for about 0.1 to about 5 hours; and then heat treating at 600°C or higher and less than about 950°C for about 0.1 to about 20 hours to produce the secondary particles. The maximum temperature of the first calcination is relative and specific to the material used for the hydroxide precursor. Optionally, in the first calcination, the maximum temperature may be 850°C or lower, optionally 720°C or lower, optionally 715°C or lower, optionally 710°C or lower, optionally 705°C or lower, and optionally 700°C or lower. Optionally, the maximum temperature of the first calcination may be about 680° C. or less. Optionally, the maximum temperature may be about 660° C. or less. Optionally, the maximum temperature may be about 640° C. or less. In yet another embodiment, the maximum temperature may be less than about 700° C., less than about 695° C., less than about 690° C., less than about 685° C., less than about 680° C., less than about 675° C., less than about 670° C., less than about 665° C., less than about 660° C., less than about 655° C., less than about 650° C., less than about 645° C., or less than about 640° C. The time at maximum temperature is optionally less than 10 hours.Optionally, the time at maximum temperature is 8 hours or less, optionally 7 hours or less, optionally 6 hours or less, optionally 5 hours or less, optionally 4 hours or less, optionally 3 hours or less, optionally 2 hours or less.
[0077] After the initial calcination, subsequent processing may include grinding the calcined material with a mortar and pestle so that the resulting powder passes through a desired sieve, optionally a #35 sieve. The powder is then optionally ball milled in a 1 gallon jar containing a 2 cm drum YSZ media, optionally for 5 minutes, or for a time sufficient to allow the material to optionally pass through a #270 sieve.
[0078] The product of the first calcination or the milled product may then optionally be treated by a method such that a stable grain boundary is obtained after the second calcination. The process of stabilizing the grain boundary and making the grain boundary electrochemical affinity for Li greater than the crystallites in the primary particles may be carried out by suspending the product of the first calcination in an aqueous slurry containing one or more substitution elements and a lithium compound, optionally at a temperature of about 60° C., whereby the substitution element is present in the aqueous solution at the concentration desired to be stabilized. The slurry is then spray dried to form a free-flowing powder, which is then subjected to a second calcination, optionally with a heating curve following a two-stage heating / holding process. Alternatively, the substitution element may be dispersed in a non-aqueous solvent together with the polycrystalline material in which it is suspended. The non-aqueous solvent may be removed by evaporation, and the substitution element precipitates on the surface of the polycrystalline material. The polycrystalline material is then subjected to a second calcination, optionally with a heating curve following a two-stage heating / holding process. The first of the two ramp / hold temperature profiles may be from ambient temperature (about 25° C.) to 450° C., optionally at a rate of 5° C. per minute, with a hold at 450° C. for one hour. The second ramp / hold step may then be from 450° C. to the maximum temperature at a rate of 2° C. per minute, with a hold at the maximum temperature for two hours. In some embodiments, the maximum temperature is about 850° C. or less.
[0079] It has been found that by combining the first calcination at the maximum temperature described above with the process of incorporating one or more substitutional elements into the grain boundaries resulting from the second calcination also described above, the resulting particles can be used in cathodes to significantly improve cycle life, reduce capacity fade and reduce impedance growth, and / or significantly improve the electrochemical performance of the material.
[0080] A cathode for a lithium ion battery comprising secondary particles is also provided. The cathode comprises the secondary particles disclosed above as an active material and may further comprise a conductive agent and a binder. The conductive agent may comprise any conductive agent that provides suitable properties and may be amorphous, crystalline, or a combination thereof. The conductive agent may comprise carbon black, such as acetylene black or lamp black, mesocarbon, graphite, carbon fiber, carbon nanotubes, such as single-walled or multi-walled carbon nanotubes, or a combination thereof. The binder can include any binder that imparts suitable properties, and can include, for example, polyvinylidene fluoride, copolymers of polyvinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), poly(methyl methacrylate-co-ethyl acrylate), polyacrylonitrile, polyvinyl chloride-co-vinyl acetate, polyvinyl alcohol, poly(1-vinylpyrrolidone-co-vinyl acetate), cellulose acetate, polyvinylpyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, sulfonated styrene / ethylene-butylene / styrene triblock polymers, polyethylene oxide, or combinations thereof.
[0081] The cathode can be made by mixing the secondary particles, conductive agent, and binder in appropriate ratios, for example, about 80 to about 98 weight percent of the secondary particles, about 2 to about 20 weight percent of the conductive agent, and about 2 to about 10 weight percent of the binder, based on the total weight of the secondary particles, conductive agent, and binder. The secondary particles, conductive agent, and binder can be suspended in a suitable solvent, such as N-methylpyrrolidone, placed on a suitable substrate, such as aluminum foil, and allowed to dry in air.
[0082] Also disclosed is a battery including the cathode. The battery may be, for example, a lithium ion battery, a lithium polymer battery, or a lithium battery. The battery may include a cathode, an anode, and a separator sandwiched between the cathode and the anode. The separator may be a microporous membrane, which may include a porous film including polypropylene, polyethylene, or a combination thereof, or may be a woven or nonwoven material such as a glass fiber mat. The anode may include a coating on a current collector. The coating may include, for example, a suitable carbon such as graphite, coke, hard carbon, or graphitized mesocarbon such as mesocarbon microbeads. The anode may also include lithium metal or a material capable of alloying (e.g., Si, Ge, etc.) or undergoing a conversion reaction (e.g., metal oxide or sulfide) with lithium. Alternatively, the anode may include lithium titanate spinel (Li4Ti5O 12 ), or a titanium-containing material such as titanium niobium oxide or titanium niobium tungsten oxide or titanium oxide. The current collector may be, for example, a copper foil or a nickel foil or a titanium foil or an aluminum foil.
[0083] The battery also includes an electrolyte that may be in contact with the positive electrode (cathode), the negative electrode (anode), and the separator. The electrolyte may include an organic solvent and a lithium salt. The organic solvent may be a linear or cyclic carbonate. Representative organic solvents include ethylene carbonate, propylene carbonate, butylene carbonate, trifluoropropylene carbonate, gamma-butyrolactone, sulfolane, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 3-methyl-1,3-dioxolane, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, propane sultone, or combinations thereof. In another embodiment, the electrolyte is a polymer electrolyte.
[0084] Representative lithium salts useful in the electrolyte include, but are not limited to, LiPF6, LiBF4, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiN(SO2C2F5)2, LiSbF6, LiC(CF3SO2)3, LiC4F9SO3, and LiAlCl4. The lithium salt can be dissolved in an organic solvent. Combinations comprising at least one of the foregoing can be used. The concentration of the lithium salt can be 0.1-2.0M in the electrolyte.
[0085] The electrolyte may be a solid ceramic electrolyte.
[0086] Various aspects of the present disclosure will now be illustrated by the following non-limiting examples. The examples are intended to be illustrative and not limiting to the practice of the invention. It will be understood that changes and modifications can be made without departing from the spirit and scope of the invention.
[0087] Working Example Example 1: Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 Y 0.02 O 2 Manufacturing and testing The overall composition is Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 Polycrystalline base material, LiO2, was synthesized by standard solid-phase synthesis techniques. 2.7 grams (g) of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) (99.9%, Alfa Aesar, Ward Hill, MA) was dissolved in 30 milliliters (ml) of methanol at 40 °C in a glass beaker. After dissolution, 35 grams (g) of polycrystalline base material (Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 O2) was added to the solution. The solution was stirred for 3 minutes to ensure distribution of the base into the methanol solution. Methanol was removed from the solution by rotary evaporation at 40 degrees Celsius (°C) and 20 mmHg.
[0088] The dried powder was placed in an alumina crucible and calcined by heating at a rate of 5°C per minute to about 130°C and then holding at about 130°C for about 6 hours. The temperature was then increased at about 5°C per minute to about 450°C and then held for about 1 hour. The temperature was then increased at about 2°C per minute to 700°C and held at about 700°C for 2 hours. The sample was then allowed to cool naturally to room temperature.
[0089] The material synthesized above was cast into a cathode electrode. This material was first mixed with PVdF, conductive carbon, and NMP solvent to prepare an electrode slurry. The electrode slurry was coated onto aluminum foil using a doctor blade method. The coated foil was dried at 130°C to drive off the NMP, leaving a coated electrode. The electrodes were then pressed, punched, and assembled into coin cells with Li metal anodes (half cells) or graphite anodes (full cells) and tested.
[0090] Comparative Example 1 The polycrystalline base material used above (Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 O2) was used as a control material without additional calcination. 1.01 Mg 0.01 Ni 0.92 Co 0.08 An electrode was prepared containing an O2 cathode powder control.
[0091] Table 3 shows the results of half cells of the electrodes of Example 1 and Comparative Example 1 tested from 4.3 volts (V) to 3.0 V, and indicates that treatment with yttrium does not significantly change the discharge capacity measured in the half cells. Figures 7 and 8 show the full cell results of accelerated cycle life measurements performed at 45°C. The material containing yttrium shows more stable cycles and significantly reduced impedance increase compared to the base material. The presence of yttrium in the grain boundary regions enhances lithium retention at the end of charge, thereby reducing damage to the material and improving cycle life at 45°C. The capacity retention and impedance increase percentage during accelerated cycle life testing at 45°C are shown in Figures 7 and 8, respectively.
[0092] [Table 3]
[0093] Example 2: Li 1.01 Mg 0.01 Ni 0.87 Co 0.11 Fe 0.02 O2 Manufacturing and Testing 0.61 g of iron acetate (Fe(C2H3O2)2) (Alfa Aesar, Ward Hill, MA) and 3.08 g of cobalt nitrate hexahydrate (Co(NO3)2 6H2O) were dissolved in 30 ml of methanol at 40 °C in a glass beaker. After dissolution, 35 g of base (Li 1.01 Ni 0.92 Co 0.08 Mg 0.01O2) was added to the solution. The solution was stirred for 3 minutes to ensure distribution of the base into the methanol solution. Methanol was removed from the solution by rotary evaporation at 40° C. and 20 mm Hg.
[0094] The dried powder was placed in an alumina crucible and calcined by heating at a rate of 5°C per minute to about 130°C and holding at about 130°C for about 6 hours. The temperature was then increased at about 5°C per minute to about 450°C and held for about 1 hour. The temperature was then increased at about 2°C per minute to 700°C and held at about 700°C for 2 hours. The sample was then allowed to cool naturally to room temperature.
[0095] Li 1.01 Mg 0.01 Ni 0.87 Co 0.11 Fe 0.02 The O2 cathode material is Li 1.01 Ni 0.92 Co 0.08 Mg 0.01 Along with an untreated base material control with O2 composition, the cells were electrochemically tested in full coin cells with a graphite anode on the other side, 1M LiPF6 in an electrolyte of 1:1:1 EC:DMC:EMC with 1% VC (EDEV1), and a polymer separator. The full coin cells were cycled between 2.7V and 4.2V at 45°C using accelerated charge and discharge rates. Figures 9 and 10 show the percentage of capacity fade and impedance increase, respectively, during the accelerated cycle life test.
[0096] Example 3: Li 1.01 Mg 0.01 Ni 0.8975 Co 0.0897 Mn 0.0128 O2 manufacturing. To enable higher levels of Li at the grain boundaries upon charging to 4.3 V, a coating with a 1 / 1 / 1 Ni / Co / Mn composition was formulated for grain boundary enrichment. LiMO2 materials with this composition are expected to retain 37% of the lithium when charged to 4.3 V vs. Li. The base material used was Li 1.01 Mg0.01 Ni 0.92 Co 0.08 O2, a 4% grain boundary enriched blend of 1 / 1 / 1 Ni / Co / Mn composition was applied, with 1.33% each of Ni, Co, and Mn relative to the total transition metal content of the base.
[0097] Manganese nitrate tetrahydrate (6.78 g), nickel nitrate heptahydrate (8.34 g), cobalt nitrate hexahydrate (7.86 g), and lithium nitrate (2.85 g) were used to prepare a 200 ml aqueous solution, which was heated to 60° C. To this, 200 g of base material was added and the dispersion was stirred for 2 minutes. The dispersion was then spray dried to produce a free-flowing powder. The powder was then calcined under a flow of CO2-free air at 700° C. for 2 hours (NCM111 enriched-sample 1) and at 715° C. for 0.25 hours (NCM111 enriched-sample 2).
[0098] The samples were then characterized for residual LiOH and average oxidation state and compared to the base material. The reduction in residual LiOH while maintaining the oxidation state strongly suggests that an ordered material was produced. Furthermore, no separate phases of LiMO2 material with NCM111 composition were detected in the XRD spectrum. Again, this suggests that the coating composition enriched the grain boundary (GB) regions rather than forming a separate NCM111 LiMO2 phase.
[0099] [Table 4]
[0100] Example 4: Li 1.01 Mg 0.01 Ni 0.8975 Co 0.0769 Al 0.0128 Mn 0.0128 O2 manufacturing. The overall composition is Li 1.01 Mg 0.01 Ni 0.92 Co 0.08A polycrystalline base cathode material (base material), consisting of NaFeO2, was synthesized by standard solid-state synthesis techniques. The grain boundaries of the base material were then enriched with elements that, in combination with nickel, form a layered 2D α-NaFeO2 structure but exhibit a significantly reduced degree of oxidation at 4.3 V. The incorporation of these elements, especially Al and Mn, was shown to promote Li retention. The bulk composition of this grain boundary Al- and Mn-enriched material (referred to as NAM111-enriched) was Li 1.01 Mg 0.01 Ni 0.8975 Co 0.0769 Al 0.0128 Mn 0.0128 The material was synthesized according to the following procedure.
[0101] Manganese nitrate tetrahydrate (3.38 g), nickel nitrate heptahydrate (3.92 g), aluminum nitrate nonahydrate (5.05 g), and lithium nitrate (1.42 g) were used to prepare a 100 ml aqueous solution, which was heated to 60° C. To this, 100 g of base material was added and the dispersion was stirred for 20 minutes. The dispersion was then spray dried to produce a free-flowing powder. This powder was then calcined at 700° C. for 2 hours under a flow of CO2-free air (NAM111 enriched).
[0102] We next analyzed the polycrystalline cathode material, NAM111 enriched, to confirm that the grain boundaries are indeed enriched in Al and Mn. Focused ion beam milling was used to create 100 nm thick sections of polycrystalline grains of NAM111 enriched. EDS line scans were performed across two different grain boundaries at the locations indicated in Figure 3. Figures 4A and B show the atomic ratios of aluminum, manganese, and cobalt to nickel across these grain boundaries. As can be seen, these grain boundaries are clearly enriched in aluminum and manganese, but not cobalt. That is, the concentration of manganese at the grain boundaries is higher than the concentration of manganese in the crystallites. Also, the aluminum concentration at the grain boundaries is higher than the aluminum concentration in the crystallites.
[0103] 4C and D show the atomic percentage of nickel relative to the total atomic content of nickel, aluminum, manganese, and cobalt across these grain boundaries. As can be seen, the concentration of nickel at the grain boundaries is lower than the concentration of nickel in the crystallites.
[0104] Example 5: Li 1.01 Mg 0.01 Ni 0.9038 Co 0.0769 Mn 0.0192 O2 manufacturing. Overall composition Li of Examples 3 and 4 1.01 Mg 0.01 Ni 0.92 Co 0.08 The same polycrystalline base cathode material with O2 (base material) was used to synthesize a material enriched in Ni and Mn at the grain boundaries (referred to as NM11 enriched). The final overall composition was Li 1.01 Mg 0.01 Ni 0.9038 Co 0.0769 Mn 0.0192 The material was synthesized according to the following procedure.
[0105] Manganese nitrate tetrahydrate (5.90 g), nickel nitrate heptahydrate (5.09 g), and lithium nitrate (1.42 g) were used to prepare a 100 ml aqueous solution, which was heated to 60° C. To this, 100 g of base material was added and the dispersion was stirred for 10 minutes. The dispersion was then spray dried to produce a free-flowing powder. This powder was then calcined at 700° C. for 2 hours under a flow of CO2-free air.
[0106] Example 6: Electrochemical testing of NCM111, NAM111, and NM11 grain boundary enriched materials. Cathode electrodes containing NCM111 enriched-sample 1 as described in Example 3, the base material and NAM111 enriched material as described in Example 4, and the NM11 enriched material of Example 5 were fabricated and electrochemically tested. The cathode active material was first mixed with PVdF binder, conductive carbon, and NMP solvent to prepare an electrode slurry. The electrode slurry was coated onto aluminum foil using a drawdown table. The coated foil was dried at 130° C. to drive off the NMP, leaving a coated electrode. The electrodes were then pressed, punched, and assembled into coin cells with Li metal anodes (half cells) or graphite anodes (full cells) and tested.
[0107] The cycle life of the three materials in full coin cells was tested using the same electrochemical procedure. Figures 11 and 12 show the capacity retention and impedance increase, respectively, during accelerated cycle life testing at 45°C. In addition to the high-rate cycling steps, a 1C continuous discharge step was included every 10 high-rate cycles. Figure 12 shows the DCR measured with a 10-s 2C pulse at the end of charge every 10 high-rate cycles. These measurements confirm the superior performance of the grain boundary enriched material in terms of both reduced capacity fade and reduced impedance increase. The selective enrichment of Al and Mn at the grain boundaries promotes additional retention of Li at the end of charge.
[0108] Example 7: XRD analysis of charged grain boundary enriched material. Figure 5 shows the homogeneous Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 O2-based materials and Li 1.01 Mg 0.01 Ni 0.8975 Co 0.0897 Mn 0.0128X-ray diffraction data for NCM111 grain boundary enriched material (Sample 1) of Example 3 with an overall composition of O2. Cathode electrodes coated on Al current collectors were X-ray analyzed either in the pristine state or charged to 4.3 V vs. Li. The electrodes were charged in coin cells opposite a Li metal counter electrode. The charged electrodes were collected, washed, and dried prior to X-ray diffraction. X-ray diffraction spectra were collected using an automated Shimadzu XRD-6000 diffractometer equipped with a Cu X-ray tube using a continuous scan from 12 to 120 degrees in 2θ at 0.75 degrees / min. The two cathode materials have essentially identical diffractograms, with many of the peaks for both materials shifting to significantly larger 2θ values upon charging.
[0109] However, comparing the XRD of the two charged materials reveals important differences. The charged grain boundaries are decorated with Li 1.01 Mg 0.01 Ni 0.8975 Co 0.0897 Mn 0.0128 The peaks at 2θ = 19° and 46° for the O2 cathode are homogeneous Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 It is broader than the O2 cathodic peak and has a shoulder at low 2θ.
[0110] The peaks at 2θ = 19° and 46° in the XRD of LiMO2 are related to the 003 and 104 crystallographic orientations of the 2D α-NaFeO2 crystal structure, respectively, which are most directly affected by the inhomogeneity of the c-axis due to the inhomogeneity of the Li distribution. Therefore, the charged grain boundary decorated Li in Figure 6 1.01 Mg 0.01 Ni 0.8975 Co 0.0897 Mn 0.0128 The low 2θ shoulder of the O2 cathode indicates that more Li is retained in the grain boundaries than in the bulk crystallites when charged.
[0111] Example 8: Li 1.01 Mg0.01 Ni 0.90 Co 0.08 Nd 0.02 O2 manufacturing. Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 Nd 0.02 Polycrystalline grain boundary enriched material with an overall composition of LiO was synthesized as follows: 2.7 grams (g) of neodymium nitrate hexahydrate (Nd(NO3)3 6H2O) (99.9%, Sigma Aldrich Milwaukee, WI) was dissolved in 30 milliliters (ml) of methanol at 40 °C in a glass beaker. After dissolution, 30 grams (g) of polycrystalline base material (Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 O2) was added to the solution. The solution was stirred for 3 minutes to ensure distribution of the base into the methanol solution. Methanol was removed from the solution by rotary evaporation at 40 degrees Celsius (°C) and 20 mmHg.
[0112] The dried powder was placed in an alumina crucible and calcined by heating at 5°C per minute to about 130°C and holding at about 130°C for about 6 hours. The temperature was then increased at about 5°C per minute to about 450°C and held there for about 1 hour. The temperature was then increased at about 2°C per minute to 700°C and held at about 700°C for 2 hours. The sample was then allowed to cool naturally to room temperature.
[0113] Example 9: Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 Ga 0.02 O2 manufacturing. Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 Ga 0.02Polycrystalline grain boundary enriched material with an overall composition of LiO was synthesized as follows: 1.55 grams (g) of gallium nitrate hydrate (Ga(NO3)3·H2O) (99.999%, Sigma Aldrich Milwaukee, WI) was dissolved in 30 milliliters (ml) of ethanol at 40 °C in a glass beaker. After dissolution, 30 grams (g) of polycrystalline base material (Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 O2) was added to the solution. The solution was stirred for 3 minutes to ensure distribution of the base into the methanol solution. Methanol was removed from the solution by rotary evaporation at 40 degrees Celsius (°C) and 20 mmHg.
[0114] The dried powder was placed in an alumina crucible and calcined by heating at 5°C per minute to about 130°C and then holding at about 130°C for about 6 hours. The temperature was then increased at about 5°C per minute to about 450°C and held there for about 1 hour. The temperature was then increased at about 2°C per minute to 700°C and held at about 700°C for 2 hours. The sample was then allowed to cool naturally to room temperature.
[0115] Example 10: Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 B 0.02 O2 manufacturing. Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 B 0.02 Polycrystalline grain boundary enriched material with an overall composition of LiO was synthesized as follows: 0.21 grams (g) of boron trioxide (BO) (99%, Sigma Aldrich Milwaukee, WI) was dissolved in 40 milliliters (ml) of methanol at 40 °C in a glass beaker. After dissolution, 30 grams (g) of polycrystalline base material (Li 1.01 Mg 0.01 Ni 0.92 Co 0.08O2) was added to the solution. The solution was stirred for 3 minutes to ensure distribution of the base into the methanol solution. Methanol was removed from the solution by rotary evaporation at 40 degrees Celsius (°C) and 20 mmHg.
[0116] The dried powder was placed in an alumina crucible and calcined by heating at a rate of 5°C per minute to about 130°C and then holding at about 130°C for about 6 hours. The temperature was then increased at about 5°C per minute to about 450°C and then held for about 1 hour. The temperature was then increased at about 2°C per minute to 700°C and held at about 700°C for 2 hours. The sample was then allowed to cool naturally to room temperature.
[0117] Example 11: Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 Fe 0.02 O2 manufacturing. Li 1.01 Mg 0.01 Ni 0.90 Co 0.08 Fe 0.02 Grain boundary enriched material with an overall composition of O was synthesized as follows: 1.23 grams (g) of ferric acetate anhydride (Fe(OOCH3)2) (99.9%, Alfa Aesar, Ward Hill, MA) was dissolved in 30 milliliters (ml) of methanol at 40 °C in a glass beaker. After dissolution, 35 grams (g) of polycrystalline base material (Li 1.01 Mg 0.01 Ni 0.92 Co 0.08 O2) was added to the solution. The solution was stirred for 3 minutes to ensure distribution of the base into the methanol solution. Methanol was removed from the solution by rotary evaporation at 40 degrees Celsius (°C) and 20 mmHg.
[0118] The dried powder was placed in an alumina crucible and calcined by heating at a rate of 5°C per minute to about 130°C and then holding at about 130°C for about 6 hours. The temperature was then increased at about 5°C per minute to about 450°C and then held for about 1 hour. The temperature was then increased at about 2°C per minute to 700°C and held at about 700°C for 2 hours. The sample was then allowed to cool naturally to room temperature.
[0119] Example 12: Electrochemical testing of the cathode materials of Examples 1 and 8-11. The cathode active materials of Examples 1, 8, 9, 10, and 11 were formulated into a cathode electrode. The materials were first mixed with PVdF, conductive carbon, and NMP solvent to prepare an electrode slurry. The electrode slurry was then coated onto an aluminum foil using a doctor blade method. The coated foil was dried at 130° C. to drive off the NMP, leaving a coated electrode. The electrodes were then pressed, punched, and assembled into coin cells with a Li metal counter electrode, a polymer separator, and a carbonate electrolyte. The half cells were then tested for capacity and rated capacity (charge to 4.3 V and discharge to 3.0 V). Electrochemical performance data for the enriched and unenriched polycrystalline base materials are shown in Table 5.
[0120] [Table 5]
[0121] Without being limited to one particular theory, as can be inferred from the above examples, it is believed that the superior cycling stability of materials with modified grain boundaries is related to the selective retention of more Li at the grain boundaries when they are charged.
[0122] Example 13: First composition LiNi 0.8 Co 0.1 Mn 0.1NCM-based materials with O2 (NCM811) were prepared from co-precipitated precursor transition metal hydroxides containing 10 at% Co, 10 at% Mn, and the balance Ni. NCA materials with first compositions of varying amounts of Ni, Co, and Al (atomic ratios of 86:12:2, 89:8:3, or 93:4:3, respectively) were prepared from co-precipitated precursor transition metal hydroxides containing the appropriate amounts of Ni, Co, and Al. Micronized LiOH powder was produced by placing 87.7 g of LiOH in a plastic jar containing 500 g of Y-stabilized zirconia 1 / 4 inch spheres and shaking on a paint shaker for 45 minutes. This micronized powder was then transferred to another plastic jar containing 335.7 g of NCM or NCA transition metal hydroxide precursor and blended by shaking the two on a paint shaker for an additional 10 minutes. After blending, approximately 440 g of powder was divided into three crucibles and fired in an oxygen atmosphere by first ramping at 5°C / min to 450°C and soaking at that temperature for 2 hours, then ramping at 2°C / min to 770°C and soaking at 770°C for 10 hours. The furnace was then cooled to 130°C and the powder was removed and placed in a ball mill. The ball mill contained 3 / 4 inch drum media, which was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve.
[0123] The sieved powder was then divided into base (without further treatment) or grain boundary enriched with Co and Al by preparing a solution of 200 g water, 11.9 g cobalt nitrate (2 at% Co with respect to the total metal content of the base composition), 3.1 g aluminum nitrate (0.4 at% Al with respect to the total metal content of the base composition) and 3.4 g lithium nitrate and then heating to 60°C. To this was added 200 g of pre-prepared lithiated precursor powder (base material). The slurry was stirred for 10 minutes and then spray dried to remove water from the slurry and prepare a dry powder. The powder was then calcined in air by first ramping at 5°C / min to 450°C and soaking at that temperature for 1 hour, then ramping at 2°C / min to 770°C and soaking for 0.25 hours. The furnace was then allowed to cool to 130° C. and the powder was removed from the furnace and sieved through a 270 mesh sieve.
[0124] The resulting base particles or grain boundary enriched particles were milled in a hydraulic press to the target pressure in a 2 cm diameter die. A total mass of 2.5 g of powder was placed in the die and milled to form pellets. The pellets were then placed in 20 mL of water and ultrasonically dispersed for 30 minutes. After dispersion, a small amount of the dispersed slurry was tested in a Malvern Mastersizer 3000 laser light particle size analyzer equipped with a liquid cell. To ensure complete dispersion of the fines, the ultrasonic function was used during the measurements and an average of five measurements was used to calculate the final results. The particle distribution was calculated using the properties of NiO taken from the instrument library. The results of this process using an exemplary NCM811 material with and without Ni-poor grain boundary regions are shown in Figure 13.
[0125] The various materials were assembled into cathodes and tested as described in Example 6. As shown in Figure 13, the presence of a relatively low concentration of Ni at the grain boundaries reduces the impedance compared to the base material.
[0126] The foregoing description of specific embodiments is merely exemplary in nature and is in no way intended to limit the scope of the disclosure or its application or use, which may of course vary. The materials and processes are described in conjunction with non-limiting definitions and terms contained herein. These definitions and terms are not intended to serve as limitations on the scope or practice of the present disclosure, but are presented for illustrative and explanatory purposes only. Although a process or composition is described as a sequence of individual steps or using specific materials, it is understood that the steps or materials may be interchangeable such that the description of the present invention may include multiple parts or steps arranged in many ways so that it can be easily understood by those skilled in the art.
[0127] Terms such as "first," "second," "third," and the like may be used herein to describe various elements, components, regions, layers, and / or portions, but it will be understood that these elements, components, regions, layers, and / or portions should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or portion from another element, component, region, layer, or portion. Thus, unless otherwise stated, a "first element," "component," "region," "layer," or "portion" described below can be referred to as a second (or another) element, component, region, layer, or portion without departing from the teachings of this specification.
[0128] The terms used herein are for the purpose of describing particular aspects only and are not intended to be limiting. As used herein, the singular forms "a," "an," and "the" are intended to include the plural, including "at least one," unless the content clearly dictates otherwise. "Or" means "and / or." As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. As used herein, the terms "comprises" and / or "comprising," or "includes" and / or "including" specify the presence of the stated features, regions, integers, steps, operations, elements, and / or components, but are further understood not to preclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and / or groups thereof. The term "or combinations thereof" refers to combinations including at least one of the aforementioned elements.
[0129] Unless otherwise specified, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. Furthermore, terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and should not be interpreted in an ideal or overly formal sense unless expressly defined in this specification.
[0130] Various modifications will be apparent to those skilled in the art from the above description, in addition to those shown and described herein, and such modifications are intended to be included within the scope of the present disclosure.
[0131] Unless otherwise specified, it is understood that all reagents are available from suppliers known in the art.
[0132] The patents, publications, and applications mentioned in this specification are indicative of the level of skill of those skilled in the art to which the disclosure pertains, and are herein incorporated by reference to the same extent as if each individual patent, publication, or application was specifically and individually indicated to be incorporated by reference.
[0133] The foregoing description illustrates certain embodiments of the present invention but is not meant to limit its practice.
Claims
1. a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; Electrochemically active particles for use in a cathode of an electrochemical cell comprising: A particle, wherein lithium is present in the grain boundaries in a higher concentration than in the crystallites when an electrode containing the particle is charged.
2. 2. The particle of claim 1, having a potential of 3.5 V or more versus lithium, optionally 4.2 V or more versus lithium, optionally 4.3 V or more versus lithium.
3. 2. The particle of claim 1, wherein lithium is present at the grain boundaries in a higher concentration than lithium in the crystallites, with a charge capacity of 40 mAh / g or greater, optionally 200 mAh / g or greater.
4. 2. The particle of claim 1, wherein the grain boundaries contain greater than 0.1 moles of lithium per mole of the second composition at the potential or capacity.
5. 2. The particle of claim 1, wherein the grain boundaries contain greater than 0.15 moles of lithium per mole of the second composition at the potential or capacity.
6. a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; Electrochemically active particles for use in a cathode of an electrochemical cell comprising: A particle wherein lithium is present at the grain boundaries in a greater concentration than within the crystallites when the particle is at a state of charge of 10 percent or greater.
7. 7. The particle of claim 6, wherein the lithium is present at the grain boundaries in a greater concentration than within the crystallites when the particle is at a state of charge of 20 percent or greater.
8. 7. The particle of claim 6, wherein the lithium is present at the grain boundaries in a greater concentration than within the crystallites when the particle is at a state of charge of 80 percent or greater.
9. a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; Electrochemically active particles for use in a cathode of an electrochemical cell comprising: the grain boundaries having a greater electrochemical affinity for lithium than the crystallites.
10. a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition comprising lithium, nickel, and oxygen; Electrochemically active particles for use in a cathode of an electrochemical cell comprising: The concentration of Ni in the second composition physically stabilizes the electrochemically active particles.
11. 11. The particle of claim 10, wherein the concentration of Ni in the second composition is sufficiently low compared to the concentration of Ni in the first composition to stabilize the electrochemically active particles such that less than 50 percent fines by number are produced when the particles are compressed at a pressure of 900 MPa.
12. 11. The particle of claim 10, wherein the Ni in the whole particle is no greater than 0.15 moles per mole of Ni in the first composition, optionally no greater than 0.1 moles per mole of Ni in the first composition.
13. The plurality of crystallites, the grain boundaries, or both are α-NaFeO 2 13. The particle of claim 1 having a layered structure, a cubic structure, a spinel structure, a monoclinic structure, or a combination thereof.
14. The second composition is Li 1+x M'O 2+y and the amount of Ni based on moles of Ni per mole of the second composition is -0≦Ni≦0.
99.
15. 15. The particle of claim 14, wherein the amount of Ni based on moles of Ni per mole of M' of the second composition is 0.9 or less.
16. 15. The particle of claim 14, wherein M' comprises an element having a higher oxidation potential than Ni.
17. The element is Li 1+x M'O 2+y 17. The particle of claim 16, wherein Ni is substitutable at the 3b site of the structure.
18. 17. The particle of claim 16, wherein the elements comprise Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, Al, or any combination thereof, optionally a concentration of the element at the grain boundary is higher than a concentration of the element in the crystallites, and optionally a concentration of Mn at the grain boundary is higher than a concentration of Mn in the crystallites.
19. 17. The particle of claim 16, wherein the elements comprise two or more elements selected from the group consisting of Mn, Ti, Cr, Fe, Co, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, and Al.
20. 17. The particle of claim 16, wherein M' comprises two or more elements selected from the group consisting of Co, Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, and Al.
21. 17. The particle of claim 16, wherein M' comprises three or more elements selected from the group consisting of Co, Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, and Al.
22. The first composition is Li 1+x M.O. 2+y and M comprises 0.1 moles of nickel or more per mole of M.
23. 23. The particle of claim 22, wherein M comprises 0.75 moles or more of nickel per mole of M, optionally 0.90 moles or more of nickel per mole of M.
24. M further comprises an additional metal, said additional metal being present in an amount of about 0.01 to about 0.90 moles per mole of M; 24. The particle of claim 23, wherein the additional metal is optionally selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof.
25. The particle further includes an outer coating on the surface thereof, the outer coating comprising: Oxides of one or more elements selected from Al, Zr, Y, Co, Ni, Mg, and Li; Fluorides containing one or more elements selected from Al, Zr, and Li; a carbonate comprising one or more elements selected from Al, Co, Ni, Mn, and Li; Sulfates containing one or more elements selected from Al, Co, Ni, Mn, and Li; or phosphates containing one or more elements selected from Al and Li; The particle of claim 1 , comprising:
26. 1. Polycrystalline electrochemically active secondary particles for use in a cathode of an electrochemical cell, comprising: The particle includes a plurality of crystallites comprising a first composition containing lithium, nickel, and oxygen, the plurality of crystallites being separated by grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries being spaced apart by Li 1+x M'O 2+y wherein Ni is present in an amount of 0≦Ni≦0.99 moles per mole of M′; The second composition is α-NaFeO 2 having a layered structure, a cubic structure, a spinel structure, a monoclinic structure, or a combination thereof; M comprises an element having a higher oxidation potential than Ni; the grain boundaries have a higher electrochemical affinity for lithium than the crystallites, or Lithium is present at the grain boundaries in a higher concentration than lithium within the crystallites when the particles are at a state of charge of 10% or more, optionally 80% or more; or When an electrode containing the particles is charged to a potential of 4.1 V or more versus lithium, lithium is present at the grain boundaries in a concentration higher than that in the crystallites; or Lithium is present at the grain boundaries in a higher concentration than lithium in the crystallites, with a charge capacity of 40 mAh / g or more with lithium, and optionally with a charge capacity of 200 mAh / g or more; particle.
27. 27. The particle of claim 26, wherein the element substitutes for Ni in the crystal structure of the grain boundary.
28. 27. The particle of claim 26, wherein the element is Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, Al, or any combination thereof.
29. 27. The particle of claim 26, wherein the elements comprise two or more elements selected from the group consisting of Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, and Al.
30. 27. The particle of claim 26, wherein M' comprises two or more elements selected from the group consisting of Co, Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, and Al.
31. 27. The particle of claim 26, wherein M' comprises three or more elements selected from the group consisting of Co, Mn, Ti, Cr, Fe, Y, Ga, Sb, W, Sc, Zr, Nb, Mo, Zn, Cu, In, Ge, and Al.
32. 32. An electrochemical cell comprising a cathode, an anode, and an electrolyte, the cathode comprising a cathode active material comprising the particles of any one of claims 1 to 31.
33. 33. The electrochemical cell of claim 32, characterized by the particles providing a discharge capacity of 170 mAh / g or greater over 200 cycles at 45°C.
34. 33. The electrochemical cell of claim 32, characterized by the particles providing a discharge capacity of 150 mAh / g or greater over 300 cycles at 45°C.
Citation Information
Patent Citations
Positive electrode active material, and lithium ion secondary battery using the positive electrode active material
JP2017204331A
Polycrystalline layered metal oxides containing nanocrystals
JP2019515437A
Positive electrode active material particles
WO2018207049A1